PENINGKATAN FUNGSI INTERMEDIASI PERBANKAN TERHADAP UMKM MELALUI JASA KONSULTAN KEUANGAN MITRA BANK (KKMB) - Sunardi Sunardi (Jurnal Keuangan dan Perbankan, 2008)
This article discusses the role of Bank partner finance consultant (KKMB) of MalangIndonesia bank (BI) in facilitating the relation pattern between micro and middle business(UMKM) and a bank. The success of KKMB can be seen from the following indicators: 1) theincrease of UMKM which is bankable and gets credit from bank, 2) the increase of quality andproductivity of UMKM finance consultant service, and 3) the growth of KKMB ability in financingitself. There is a different perception between banks and UMKM. Banks consider that UMKMhas not deserved to be given credit facility because it has not fulfilled the requirements frombanks. However, UMKM considers that banks are always guided by rules which are difficult forUMKM to fulfill it. In this condition, the existence of KKMB is as a mediator for both sides.KKMB has a function to increase the administration quality of UMKM so it can be bankable.One of obstacles faced by UMKM is in collateral. To overcome this problem, Malang IndonesiaBank (BI) through UPT (Technique Implementer Unit) asks KKMB as the implementer of massland certification which corporates with district, Batu city BPN, and Bukopin.